2020
DOI: 10.1001/jamanetworkopen.2020.8263
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of Brief Screening Tools to Identify Impaired Driving Among Older Adults in Australia

Abstract: IMPORTANCE There is an urgent need to develop evidence-based assessments to identify older individuals who may be unsafe drivers. OBJECTIVE To validate 8 off-road brief screening tests to predict on-road driving ability and to identify which combination of these provides the best prediction of older adults who will not pass an on-road driving test. DESIGN, SETTING, AND PARTICIPANTS This prognostic study was conducted between October 31, 2013, and May 10, 2017, using the criterion standard for screening tests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Congregated analyses of individual such reports allow putting our individual results in a bigger context [ 22 , 23 , 29 ], although data sets diverge vastly either in size, outcome measure, combination of test, or prevalence of unsafe driving. This prompts justified efforts to compare a wide range of tests in forward-studies under the same conditions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congregated analyses of individual such reports allow putting our individual results in a bigger context [ 22 , 23 , 29 ], although data sets diverge vastly either in size, outcome measure, combination of test, or prevalence of unsafe driving. This prompts justified efforts to compare a wide range of tests in forward-studies under the same conditions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As compared to other approaches trying to provide comprehensive and cost-effective tools to potentially complements or – wherever necessary– replace on-road performance tests, our analysis and resulting data are clearly neither intended nor by any means strong enough to replace MSDT. Large scale validation studies do show that such tools can reliably identify those elderly drivers with a high likelihood of failing on road tests, be it due to dementia [ 43 ], or due to (mild) cognitive or visual impairment [ 33 ]. In addition, off-road screening tools for safe driving in the elderly could be shown to benefit both time- and cost-wise from including also from simple non-cognitive information, such as number of medication taken per day, cervical spine mobility, impaired visual acuity or field of view and avoidance behavior, while maintaining high validity to results from on-road testing [ 26 , 27 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous hazard perception tests used one-screen or three-screen monitors, limiting users' visual field [6,8,9,[11][12][13][33][34][35][36]. In terms of situation awareness theory [15,16], the hazard perception test needs to be conducted in the actual driving situation due to its requirement of reproducing the visual field of actual driving.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of hazard perception is an important area to be completed in clinical practice. Among the various driving tests in rehabilitation, the hazard perception test, the useful field of view test, and the Multi-D battery are recommended driver's tests in Australia in terms of their high reliability and high level of evidence [11]. A previous study that included subjects with hemianopia showed that a significant number of subjects could not identify hazards on their blind side [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the Original Investigation titled “Validation of Brief Screening Tools to Identify Impaired Driving Among Older Adults in Australia,” 1 published June 17, 2020, there was an error in the Methods in the description of the maze test used. The correct maze test is Occupational Therapy—Driver Off Road Assessment maze test.…”
mentioning
confidence: 99%